2011
DOI: 10.1590/s0102-86502011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Protocols for obtainment and isolation of two mesenchymal stem cell sources in sheep

Abstract: Purpose:To evaluate different protocols to isolate stem cells from ovine umbilical cord blood and adipose tissue. Methods: There were used 5 samples of umbilical blood and 5 samples of perirenal adipose tissue from 10 female sheep. All the samples were obtained through surgery, to harvest aseptic samples. There were used 3 protocols for obtainment and culture of umbilical cord blood stem cells and 4 protocols for ovine adipose tissue stem cells. Results: It was possible to observe only one successful protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 26 publications
2
27
0
3
Order By: Relevance
“…The cell population with the fusiform appearance described here in samples from both adipose tissue and bone marrow were morphologically similar to mesenchymal stem cells from human (Zuk et al 2001, You et al 2009), sheep (Fadel et al 2011), horse (Fortier et al 1998, Smith et al 2003, Hegewald et al 2004, Vidal et al 2006, 2007, Maia et. al 2012, De Vita et al 2013, and other animals reported in many studies, in which these cells were described as star-shaped or fibroblast-like.…”
Section: Discussionsupporting
confidence: 63%
“…The cell population with the fusiform appearance described here in samples from both adipose tissue and bone marrow were morphologically similar to mesenchymal stem cells from human (Zuk et al 2001, You et al 2009), sheep (Fadel et al 2011), horse (Fortier et al 1998, Smith et al 2003, Hegewald et al 2004, Vidal et al 2006, 2007, Maia et. al 2012, De Vita et al 2013, and other animals reported in many studies, in which these cells were described as star-shaped or fibroblast-like.…”
Section: Discussionsupporting
confidence: 63%
“…However, harvesting MSCs from heterogenous cell population still remains one of the challenging tasks that are worth considering (Fekete et al, 2012;Harichandan and Buhring, 2011;Hsu et al, 2012). Despite of several advancement and sophistication for MSC isolation was made in case of human and small laboratory research animal, a standard and convenient method of isolating MSCs from large domestic animal (Fadel et al, 2011;Stewart et al, 2007) still need to be optimized. De Schauwer et al (2014) reported the non-invasive sources of MSCs such as umbilical cord blood, umbilical cord matrix and peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding such animals, outcomes were found in studies about neurodegenerative injuries 12,13 , as well as in attempts to use cell therapy as a way to treat cardiovascular diseases 20 . Experiments with sheep were described for obtaining the main uses of stem cells/progenitor cells 21,22 . However, such potentialities have been little studied in the goat species.…”
Section: Introductionmentioning
confidence: 99%